Rich dad's guide to investing : what the rich invest in, that the poor and middle class do not! - Kiyosaki, Robert T., 1947-; Lechter, Sharon L. (Scottsdale, Ariz. : TechPress, 2000)
Are you mentally prepared to be an investor? What type of investor do you want to become? How do you build a strong business. Who is the sophisticated investor?
Keywords: Finance; Economics; Investments; Success; Wealth; Business education; Investments; Finance, Personal